PELATIHAN HANDLING COMPLAINT PADA UNIT FRONT OFFICE DI HOTEL UPT DESTINASI WISATA TERPADU KABUPATEN JEMBER - Rinda, Renata Kenanga; Nodistya Septian Indrastana; Vigo Dewangga; Enik Rukiati; Yuslaili Ningsih (Bajang Institute, 2025)
Tourism is one sector that makes a significant contribution to the economic development in Kabupaten Jember. Therefore, this sector needs to be prioritized. To address the previous statement, special attention is needed for supporting accommodations, including hotels. One of the hotels in Kabupaten Jember is managed by UPT Destinasi Wisata Terpadu Rembangan. Through an interview process with front office staff, this hotel has been able to provide services to local and international communities. However, service quality is considered less than optimal, especially in handling complaints delivered by the international customers. Therefore, this training entitled Handling Complaint Training for the Front Office Staff of Hotel UPT Destinasi Wisata Terpadu was orgnized using English. The training was carried out using the scientific approach method by applying five stages, namely observing, questioning, associating, experimenting, and communicating over a period of six months. It is hoped that with this training, the understanding and quality of complaint handling are increased.